1997
DOI: 10.1002/(sici)1098-2736(199712)34:10<1019::aid-tea4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a gender and ethnic equity in science education curriculum for preservice teachers

Abstract: The purpose of the Gender and Ethnic Equity in Science Education (GEESE) program, conducted during the student-teaching semester, was to provide preservice science teachers with the opportunity to use clinical observations and reflection as vehicles for discovery of the disparate school experiences of the diverse students in their science classrooms. The preservice teachers examined curricular materials in use during their practicum, student and teacher behaviors, the quantity and quality of student-teacher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Several papers, taken together, illustrate the range of new teachers' knowledge of or ideas about approaches for teaching science for all (Arellano et al, 2001;Bianchini & Solomon, 2003;Bullock, 1997;Howes, 2002;McDevitt et al, 1995;Rodriguez, 1998;Sweeney, 2001). Rodriguez, for example, studied 18 preservice secondary teachers, including 4 focus teachers, and found that the preservice teachers tended to feel hopeless and overwhelmed about working with diverse students.…”
Section: Diverse Learners and Science For Allmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers, taken together, illustrate the range of new teachers' knowledge of or ideas about approaches for teaching science for all (Arellano et al, 2001;Bianchini & Solomon, 2003;Bullock, 1997;Howes, 2002;McDevitt et al, 1995;Rodriguez, 1998;Sweeney, 2001). Rodriguez, for example, studied 18 preservice secondary teachers, including 4 focus teachers, and found that the preservice teachers tended to feel hopeless and overwhelmed about working with diverse students.…”
Section: Diverse Learners and Science For Allmentioning
confidence: 99%
“…Science methods courses and teacher education programs also help preservice teachers to develop improved understandings of and attitudes toward science (e.g., Hynd et al, 1997;Palmer, 2002;Strawitz, 1993), learners (e.g., McDevitt et al, 1995Rodriguez, 1998;Yerrick & Hoving, 2003), diverse learners and science for all (e.g., Bailey, Scantlebury, & Johnson, 1999;Bullock, 1997;Fraser-Abder, 2001;Richmond et al, 1998;Rodriguez, 1998), and learning environments (e.g., Adams & Krockover, 1997a), as well as promoting self-efficacy (Huinker & Madison, 1997;King & Wiseman, 2001). Science teacher educators recommend innovations as wide-ranging as drawing science concept cartoons (Naylor & Keogh, 1999), writing about one's science learning experiences (Van Zee & Roberts, 2001), and listening to experienced science supervisors' stories about new teachers (Zuckerman, 1999).…”
Section: Supportive Preservice Teacher Educationmentioning
confidence: 99%
“…Another approach was to have preservice students tutor children in cultural contexts that are not primarily White and middle-class (Aaronsohn, Carter, & Howell, 1995;Barton, 1999;Boyle-Baise & Sleeter, 2000;Bullock, 1997;Lazar, 1998;Moule, in press;Murtadha-Watts, 1998;Rodriguez, 1998). These case studies described insights that specific preservice students gained, including their growth in awareness of culture, knowledge of a context different from their own, and awareness of their own stereotypes.…”
Section: Multicultural Education Coursework With a Field Experiencementioning
confidence: 99%
“…Teachers often leave education programs with misconceptions about the history and culture of groups other than their own that are incomplete, misleading, and chauvinistic. Without intervention, these entering beliefs will continue to shape their ideas and practices within the classroom (Banks, 1991;Bullock, 1997;Feiman-Nemser, 2001;Zeichner, 1993). One of the current practices suggested is that of having preservice teachers explore their own cultural identities by writing autobiographies (Banks, 1991;Feiman-Nemser, 2001;Zeichner, 1993).…”
Section: Guiding Literaturementioning
confidence: 99%
“…Equitable representation in curricular materials; equitable opportunities in the laboratory setting; and equitable evaluation of student performance are important information for prospective teachers to know (Bullock, 1997). Bullock also believes that preservice teachers are more apt to respond to novel instruction if it is presented in teacher training programs.…”
Section: Guiding Literaturementioning
confidence: 99%